Answer:
( , - 3 )
Step-by-step explanation:
Given the 2 equations
6x - y = 23 → (1)
3y + 6x = 11 → (2)
Subtracting (2) from (1) term by term eliminates the term in x
(6x - 6x) + (- y - 3y) = (23 - 11), that is
- 4y = 12 ( divide both sides by - 4 )
y = - 3
Substitute y = - 3 into either of the 2 equations and solve for x
Substituting in (1)
6x - (- 3) = 23
6x + 3 = 23 ( subtract 3 from both sides )
6x = 20 ( divide both sides by 20 )
x = =
Solution is ( , - 3 )
Output (y)
1 12
3 9
5 6
? ?
(7, 3)
(7, 10)
(3, 3)
(3, 10)
Answer:
Your answer would be A (7,3)
Answer:
x-2
Step-by-step explanation:
photomath app
Answer:
12/2g + 1
Step-by-step explanation:
Answer:
12/2g + 1
trust me i know this
y varies directly with x, and y=2. What is the value of y when x=5?